Pengaruh Kualitas Pelayanan Rawat Inap Dengan Tingkat Kepuasan Pasien Di RSUD Kota Makassar - Muhajirin Muhajirin; Arfiah Jauharuddin (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Service quality is the level of perfection in meeting consumer needs. Satisfaction is the feeling of pleasure or disappointment that someone experiences after comparing the performance or results of a product with their expectations. This study aims to analyze the relationship between inpatient service quality and patient satisfaction levels at the Makassar City Regional Hospital. The research method used was descriptive analytical with a cross-sectional design. The instrument used was a questionnaire regarding inpatient service quality and patient satisfaction levels. The study population consisted of inpatients in the Internal Medicine Department of the Makassar City Regional Hospital in October 2023. The sample consisted of 67 individuals according to predetermined criteria. The data collected were analyzed using the Spearman Rank statistical test with a significance level of 0.05. The majority (38.81%) of patients stated that the quality of service provided was high and 68.66% of patients claimed to be satisfied. The analysis results showed that the calculated r value was 0.627, which is greater than the tabled r value of 0.364. From these analysis results, it can be concluded that there is a relationship between inpatient service quality and patient satisfaction levels.